The relationship between demographic factors and job satisfaction based on maslow theory of needs in Philips semiconductors Seremban / Fazarina Mohd Pauzi - Mohd Pauzi, Fazarina (Faculty of Business and Management, 2006)
Workforce is the most important factor and to maintain sustainable long-term competitive advantage of organization. The purpose of this project paper is to examine the level of satisfaction among the workers in the organization, to examine demographic factors that related to job satisfaction, to identify the factors contributing to job satisfaction based on Maslow Theory of Needs, and to give recommendation and strategies to solve the problem. Researcher used Descriptive Design and Convenient Non-Probability Sampling for this research. A set of questionnaire was distributed to 100 of respondents in Philips Semiconductors Seremban. When considering job satisfaction, demographic variables should be considered to thoroughly understand the possible factors that lead to job satisfaction and dissatisfaction. The analysis on level of satisfaction has determined satisfaction level of the employee towards their work and organization. Based on 63 usable responses, most of them are satisfied working in Philips Semiconductors Seremban. Researcher has stated several recommendations and suggestions that may be useful to improve organization's strategies in the future.